The effect of reduction of door-to-needle times on the administration of thrombolytic therapy for acute myocardial infarction. Issue 875 (September 1998) - Kelion, A. D.; Banning, A. P.; Shahi, M.; Bell, J. A.
Abstract : Optimal management of acute myocardial infarction requires rapid administration of thrombolytic therapy. However, only patients who fulfill the following specific criteria are likely to benefit from this treatment: admission within 12 hours of the onset of symptoms, no contraindications, ST elevation or possible new-onset left bundle branch block on the admission electrocardiogram. We employed an aggressive policy to reduce the delay between admission to hospital and the administration of thrombolysis (the 'door-to-needle time'), and investigated whether this approach affected the accuracy of administration of thrombolysis. Patients admitted to the cardiac care unit with acute myocardial infarction, or who were thrombolysed, were identified retrospectively over two equivalent 4-month periods before and after implementation of our policy. Patients were considered eligible for thrombolysis if they fulfilled the criteria mentioned above. The mean (SD) door-to-needle time for all patients who received thrombolysis on admission decreased from 61(70) to 19(20) minutes (p = 0.0004). The proportion of patients eligible for thrombolysis who received treatment increased from 24/38 to 30/30 (p = 0.0002). However, the proportion of patients receiving thrombolysis who did not fulfill our criteria also increased, from 3/27 to 11/41 (p = 0.1). There were no complications of thrombolysis in the first study period, but two cerebrovascular accidents in the second period; both patients fulfiled our criteria for treatment. We conclude that simple educational measures greatly reduced door-to-needle times and led to a higher proportion of eligible patients receiving thrombolysis. However, greater pressure on medical staff to make rapid management decisions increased the proportion of patients being thrombolysed inappropriately.